Evaluating allergic sensitization in pediatric patients: A cross-sectional multicentric analysis - V. Y. Jayakrishnan; Rabindra Bhunia; Sangeetha Balumani; R. Krishna Mohan; Neha Saxena; Anil Kumar (Indian Journal of Allergy Asthma and Immunology)
OBJECTIVES: The study aims to outline the allergic sensitization patterns among pediatric patients presenting with allergic manifestations in the allergy clinics of three Indian Armed Forces hospitals one each from North, West, and South India. It seeks to identify the common allergens affecting children aged 1–14 years who exhibit symptoms of allergic conditions. In addition, it evaluates the clinical manifestations associated with various allergen exposures and aims to provide valuable insights for personalized management and preventive strategies in managing allergic diseases. METHODS: A cross-sectional study involving a detailed examination of children aged 1–14 years who presented with symptoms of allergic diseases such as allergic rhinitis (AR), asthma, eczema, and allergic conjunctivitis (AC). Skin prick tests were utilized to identify sensitization to common allergens including house dust mites (HDMs), pollens, spores, animal dander, and food allergens. RESULTS: The findings revealed that HDMs were the predominant allergens, followed by cockroach, mosquito, pollens, and animal dander. Clinical manifestations varied across different allergen exposures, with notable differences in the presentation of AR, asthma, eczema, and AC among the patients. CONCLUSION: This research underscores the importance of early diagnosis, targeted management, and preventive measures in mitigating the impact of allergies on children’s health. It highlights the necessity for healthcare providers in military settings to be aware of regional allergen patterns and adapt their clinical practices accordingly to improve patient outcomes.